Women Participation in Livestock Raising and Household Managemnt In Rural Communities of Nafada, Semi-Arid Region Of Northeastern Nigeria - Dan , Yakubu; Kim, Idoma (Advances in Social Sciences Research Journal, 2020)
This study was carried out to examine women’s participation in livestock raising in rural communities of Nafada, semi-arid region of Northeastern Nigeria. Thirteen villages were purposively sampled, and 10 women respondents were randomly selected from each village. Standardized interview schedule was adopted in the collection of information from the sampled respondents and analyzed using descriptive statistics and Pearson Product Moment Correlation. The results disclosed that approximately half (45%) of the respondents raised goats and sheep and 100% were involved regularly in cleaning of animal sheds, watering and grazing of animals. In addition, washing of clothes, food preparation, cleaning of the house, looking after all family members, child/family health care, preparing beverages and cleaning up after meals ranked highest among household activities undertaken by women. Major challenges of livestock raising, and household management were low innovation (ranked 1), rustling (ranked 2), ranching (ranked 2) and health of animals (ranked 2). Others included child/family care (ranked 1), food (ranked 1), fuel wood collection (ranked 3) and absence of funding from government agents. The correlation results revealed that family size and education of respondents were significant factors influencing the extent of women’s participation in livestock raising in the study area. Therefore, carefully targeted women-focused programmes on livestock farming, intensive adult education and improved agricultural extension/ veterinary services among others are crucial to improving women’s participation in livestock production in Nafada LGA.